Testing the Arabic-Saudi Arabia version of the Rome IV Diagnostic Questionnaire for functional gastrointestinal disorders for Children living in Saudi Arabia - Khatib, Mai A.; Aljaaly, Elham A. (Frontiers in Pediatrics, 2023)
Functional gastrointestinal disorders (FGID) are a worldwide phenomenon described by painful, recurrent or chronic gastrointestinal (GI) symptoms. Variable types of FGID exist in a significant portion of children in Saudi Arabia (SA). While the studies and reports on child FGID are limited, the available ones show a notable significance of FGID in children in SA. The self-report Rome IV Diagnostic Questionnaire (DQ) globally recognizes the selection of symptom criteria and incidence thresholds. Using such a questionnaire would help clinicians provide a provisional diagnosis, serve as a case definition for epidemiological surveys, and identify inclusion criteria for clinical trials. This research aimed to pilot test the collective FGIDs prevalence among preschool children in Jeddah city and its countryside of Saudi Arabia, using Rome IV DQ in Arabic-SA. Of the 59 responses, 11.8% (n=7), 5% (n=3), 1 (1.6%), and 1 (1.6%) participants have functional dyspepsia, functional constipation, functional irritable bowel syndrome, and functional aerophagia, respectively, according to the Rome IV criteria. The tested translated DQ in this study was the first translated version available in Arabic- SA, which could provide researchers and clinicians in SA with a diagnostic tool for FGIDs. However, because this study is a pilot study in a new field, the conclusions cannot be extrapolated to the demographic of the targeted population of children. The same researchers plan a larger study to use the current results and a larger calculated sample to assess FGIDs prevalence in children 4+ years old in Jeddah and its countryside, Saudi Arabia.